THE ROLE OF COMPUTER TECHNOLOGY IN HUMAN LIFE. (Лучшие интеллектуальные исследования, 2025)
Annotation: Computer technology is an emerging field of engineering that helps in the activity of designing, constructing, and programming computers. It is the combination of both hardware and software that makes it easier for the user to solve complex and dynamic problems efficiently. The different types of computer hardware and software are known to perform specific functions, like running programs, repairing computer systems, and installing computer networks. This field of study is directly connected with information technology, and it covers a developing list of numerous software system designs and programs.